Physical activity level and health-related quality of life (HRQOL) in amateur tennis players. Comprehensive evaluation of factors and components of subjective self-assessment of health - Kocjan, Janusz (Journal of Education, Health and Sport, 2015)
Kocjan Janusz. Physical activity level and health-related quality of life (HRQOL) in amateur tennis players. Comprehensive evaluation of factors and components of subjective self-assessment of health. Journal of Education, Health and Sport. 2015;5(6):375-383. ISSN 2391-8306. DOI 10.5281/zenodo.18779 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A375-383 https://pbn.nauka.gov.pl/works/568290 http://dx.doi.org/10.5281/zenodo.18779 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 20.06.2015. PHYSICAL ACTIVITY LEVEL AND HEALTH-RELATED QUALITY OF LIFE (HRQOL) IN AMATEUR TENNIS PLAYERS. COMPREHENSIVE EVALUATION OF FACTORS AND COMPONENTS OF SUBJECTIVE SELF-ASSESSMENT OF HEALTH JANUSZ KOCJAN Medical University of Silesia, Faculty of Medicine, Katowice, Poland SUMMARY Introduction: Physical recreation is an active form of leisure time spending. The rapid development of science and technology, which has been made over the last few decades, and the following as a result of changes in circumstances and ways of people life caused that growing number of people are deciding for sedentary form of free-time spending. Regular physical activity is regarded not only as one of the key factors of health prevention, but also allows to the proper functioning of the body in physically and mentally dimension. The purpose of this study: was to evaluate the level of physical activity of amateur tennis and the level of their quality of life compared to people not engaged in sports activities. It was also examined whether the level of physical activity, age and BMI affect different dimensions and components of health in both groups. Material and methods: The study involved 81 men aged 18-62 years (M=46,24; SD=10,43) - participants of amateur tennis tournaments. The control group consisted of 108 men aged 23-57 years (M=39,76; SD=7,98), who do not take any physical activities in the past and have no any somatic diseases. The study used sociometric techniques complemented by the own designed author's questionnaire. The level of sport activity was determined using a HPA (Habitual Physical Activity) questionnaire, while health self-assessment using a SF-36 (Short Form Health Survey) questionnaire. Results: Significantly higher self-assessment of health was noted in the tennis sample – compared to the control group. Positive correlations between sport index ang global HPA index with factors and components of health were reported. In case of control group, relationships were weaker and additionally concern impact of work index to mental component of health and mental factors. In both group, association between age and BMI index with health self-assessment was no found. Conclusions: Regular physical activity has a positive effect on physical and mental functioning of the body. Age and BMI did not show a connection with dimensions and components of health. Keywords: physical activity, self-assessment of health, quality of life, tennis. STRESZCZENIE Wstęp: Rekreacja ruchowa jest formą aktywnego spędzania wolnego czasu. Szybki rozwój nauki i techniki, który dokonał się na przestrzeni ostatnich kilkudziesięciu lat, oraz następujące w wyniku tego zmiany warunków i sposobów życia ludzi spowodowały, iż coraz więcej osób decyduje się na sedenteryjny tryb wypoczynku. Systematyczna aktywność fizyczna, uważana jest nie tylko jako jeden z kluczowych czynników profilaktyki zdrowia, lecz pozwala również na prawidłowe funkcjonowanie organizmu w wymiarze fizycznym oraz psychicznym. Cel pracy: Celem pracy była ocena poziomu aktywności fizycznej osób amatorsko uprawiających tenis ziemny oraz określenie poziomu ich jakości życia w porównaniu do osób nie prowadzących aktywności sportowej. Zbadano także czy poziom aktywności fizycznej, wiek oraz wartość wskaźnika BMI wpływają na poszczególne wymiary i komponenty zdrowia w obu grupach. Materiał i metody: Badaniem objęto 81 mężczyzn w wieku 18-62 lat (M=46,24; SD=10,43) – uczestników amatorskich turniejów tenisowych. Grupę kontrolną stanowiło 108 mężczyzn w wieku 23-57 lat (M=39,76; SD=7,98), nie prowadzących żadnej aktywności fizycznej oraz nie leczących się na żadną chorobę somatyczną. W badaniu wykorzystano techniki socjometryczne uzupełnione o autorską metryczkę. Poziom aktywności sportowej określono za pomocą kwestionariusza HPA (Habitual Physical Activity) natomiast samoocenę zdrowia za pomocą kwestionariusza SF-36 (Short Form Health Survey). Wyniki: Odnotowano istotnie statystycznie wyższą samoocenę samoocenę zdrowia w grupie badanej – w porównaniu z grupą kontrolną. Zaobserwowano dodatnią korelacje między wskaźnikiem sportu i ogólnym wskaźnikiem HPA a czynnikami i komponentami zdrowia wśród mężczyzn uprawiających sport. W odniesieniu do grupy kontrolnej, odnotowano negatywną zależność między wysiłkiem fizycznym w pracy a psychicznym komponentem zdrowia i tworzącymi go czynnikami. W obu grupach, wiek i wartości wskaźnika BMI nie korelują ani z samooceną zdrowia ani z aktywnością fizyczną. Wnioski: Systematyczna aktywność fizyczna pozytywnie wpływa na funkcjonowanie fizyczne i psychiczne organizmu. Wiek oraz wartości wskaźnika BMI nie wykazują związku z wymiarami i komponentami zdrowia. Słowa kluczowe: aktywność fizyczna, samoocena zdrowia, jakość życia, tenis ziemny.